Vaccines Through Centuries: Major Cornerstones of Global Health - Hajj Hussein, Inaya; Chams, Nour; Chams, Sana; El Sayegh, Skye; Badran, Reina; Raad, Mohamad; Gerges-Geagea, Alice; Leone, Angelo; Jurjus, Abdo (Frontiers in Public Health, 2015)
Multiple cornerstones have shaped the history of vaccines, which may contain live-attenuated viruses, inactivated organisms/viruses, inactivated toxins, or merely segments of the pathogen that could elicit an immune response. The story began with Hippocrates 400 B.C. with his description of mumps and diphtheria. No further discoveries were recorded until 1100 A.D. when the smallpox vaccine was described. During the eighteenth century, vaccines for cholera and yellow fever were reported and Edward Jenner, the father of vaccination and immunology, published his work on smallpox. The nineteenth century was a major landmark, with the “Germ Theory of disease” of Louis Pasteur, the discovery of the germ tubercle bacillus for tuberculosis by Robert Koch, and the isolation of pneumococcus organism by George Miller Sternberg. Another landmark was the discovery of diphtheria toxin by Emile Roux and its serological treatment by Emil Von Behring and Paul Ehrlih. In addition, Pasteur was able to generate the first live-attenuated viral vaccine against rabies. Typhoid vaccines were then developed, followed by the plague vaccine of Yersin. At the beginning of World War I, the tetanus toxoid was introduced, followed in 1915 by the pertussis vaccine. In 1974, The Expanded Program of Immunization was established within the WHO for bacille Calmette–Guerin, Polio, DTP, measles, yellow fever, and hepatitis B. The year 1996 witnessed the launching of the International AIDS Vaccine Initiative. In 1988, the WHO passed a resolution to eradicate polio by the year 2000 and in 2006; the first vaccine to prevent cervical cancer was developed. In 2010, “The Decade of vaccines” was launched, and on April 1st 2012, the United Nations launched the “shot@Life” campaign. In brief, the armamentarium of vaccines continues to grow with more emphasis on safety, availability, and accessibility. This mini review highlights the major historical events and pioneers in the course of development of vaccines, which have eradicated so many life-threatening diseases, despite the vaccination attitudes and waves appearing through history.